Why did Byron have to write Cain before he could finish The Vision of Judgement?. Issue 2 (December 2015) - Cochran, Peter
Abstract : This paper argues that Byron's writing of his mystery play Cain was crucial for the successful composition of the brilliant and dramatically superior satire The Vision of Judgement, which followed only after the completion of Cain . Peter draws on manuscript evidence as well as intertextual echoes in the two divergent works to suggest their intricate interrelatedness.